Prophylactic Cranial Irradiation in Extensive Small-Cell Lung Cancer - Slotman, Ben; Faivre-Finn, Corinne; Kramer, Gijs; Rankin, Elaine; Snee, Michael; Hatton, Matthew; Postmus, Pieter; Collette, Laurence; Musat, Elena; Senan, Suresh (The New England journal of medicine, 2007)
Symptomatic brain metastases are a major clinical problem in small-cell lung cancer. This trial compared prophylactic cranial irradiation with observation in patients with small-cell lung cancer who had had any response to chemotherapy. Prophylactic irradiation reduced the risk of symptomatic brain metastases and was associated with longer overall survival. Prophylactic cranial irradiation reduced the risk of symptomatic brain metastases and was associated with longer overall survival. Small-cell lung cancer constitutes nearly 13% of all newly diagnosed lung cancers. 1 Most patients present with extensive disease, and without treatment, the median survival is 2 to 4 months. Chemotherapy has improved short-term survival, but long-term survival remains disappointing. The 2-year survival rate among patients with extensive small-cell lung cancer was 1.5% in 1973 and 4.6% in 2000. 1 Brain metastases are common in this disease. At diagnosis, at least 18% of patients have brain metastases, 2 and the incidence of such metastases increases considerably during the course of the disease, approaching 80% at 2 years. 3 The presence of brain metastases is . . .